Social justice and technocracy: tracing the narratives of inclusive education in the USA. Issue 4 (3rd July 2016) - Danforth, Scot
ABSTRACT: Over the past two decades, the percentage of American students with disabilities educated in general classrooms with their nondisabled peers has risen by approximately 50%. This gradual but steady policy shift has been driven by two distinct narratives of organisational change. The social justice narrative espouses principles of equality and caring across human differences. The narrative of technocracy creates top-down, administrative pressure through hierarchical systems based on quantitative performance data. This article examines these two primary policy narratives of inclusive education in the USA, exploring the conceptual features of each and initiating an analysis of their application in the public schools.